Green nanocomposites for environmental sensors in smart grid systems - Heidari, Fatemeh; Salimi , Zahra; Moradi, Fateme (Journal of Composites and Compounds, 2025)
Green nanocomposites are advanced materials that integrate environmentally friendly and sustainable components, such as biopolymers or green-synthesized nanoparticles, to create functional nanomaterials with low toxicity and high eco-compatibility. These materials are increasingly used in environmental sensor technologies due to their enhanced sensitivity, stability, and sustainable synthesis routes. In smart grid systems, green nanocomposites play a crucial role by enabling real-time environmental monitoring with minimal environmental impact, supporting energy efficiency and renewable integration. Smart sensors provide accurate tracking of energy usage trends, enhance load distribution, and advance the sensible application of renewable energy resources. These sensors aid in cutting down on energy waste and by interacting with customers and enabling demand-response systems. Smart grids benefit from sensors made with green nanocomposites for dynamic monitoring of environmental parameters influencing energy generation and consumption. These sensors, embedded in smart home and grid infrastructure, optimize energy efficiency and renewable integration by providing precise data on pollution, temperature, and other conditions. Optimization algorithms in smart grids leverage this sensor data to reduce waste and enhance system reliability. This study demonstrates the role of green nanocomposites in environmental sensors of smart grid systems.